French Islamophobia: The Impact of Islamophobia on The Lives of Muslim Women in France - Azmi, Agus Nilmada; Aisy, Aufa Rahadatul (Mimbar Agama Budaya, 2023)
Islamophobia is not a new phenomenon. Scholars and authors have been portraying Islam negatively for a long time. Islamophobia was prevalent during the European colonial era and reappeared with a vengeance following the 9/11 attacks, which gave rise to the "war on terror" campaign. The Islamic threat became a broader ideology and even officially entered French dictionaries. The bad stereotypes that are spread about Islam have increased Islamophobia in French society, which has had an impact on the lives of Muslims in France. Pressure and discrimination are familiar things to Muslims in France. The policies implemented by the government also have a discriminatory tendency towards Muslims. This article further analyses the specific impacts experienced by French Muslim women in everyday life, such as discrimination in the world of work, experiences of bullying in public spaces, and conflicts with negative stereotypes that are often attached to their identity. This article aims to provide a comprehensive understanding of the phenomenon of Islamophobia in France and how this can affect the lives of Muslim communities especially Muslim women in France.